Detection Of Candida Albicans Responsible For Vulvovaginitis In Women - Taher, Sherihan K. (AL-Kindy College Medical Journal, 2019)
Background: The vaginal microbial ecosystem stability preclude many other organisms but sometimes the vaginal micro biota is disturbed and this cause change in the normal balance causing symptoms of vulvuvaginitis like abnormal or increased vaginal discharge, redness and itching. Objective: To prove C. albicans presence in their vagina clinically and laboratory by culture of vaginal swab on two media. Type of the study: This study is a case control study Methods: This study is a case control study in which 100 clinically patient women admitted to maternity hospital in kalar city and khanaqin hospital during the period from 1st August– 30th of October 2016 who were examined to prove C. albicans presence in their vagina clinically and laboratory by culture of vaginal swab on two media, the first media was used for primary isolation which was Sabouraud´s dextrose agar media and the second was to differentiate Candida spp. according to their color . Results: Results of this study presented that the highest invasion of the vagina of Candida spp was accounted for C. albicans (39.6%)from the (53) positive cultures , while other species were as follows: C. glabrata (26.4%), C. tropicalis (20.8%) ,C. krusi(13.2 %). Conclusions: this study presented that the highest invasion of the vagina of Candida spp was accounted for C. albicans